The effect of using the survey strategy on the achievement of environmental education among students of the College of Education - Rese.Asaad Musa Hashem; Prof. Dr. Ismail Hassan Abdullah (Journal of College of Education, 2024)
The current research aims to identify the effect of using the survey strategy on the achievement ofenvironmental education among first-stage students in the College of Education. To achieve this goal, the researcher formulated the following zero hypothesis.                             :There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group (who studied the environmental education subject using the survey strategy) and the mean scores of the students of the control group (who studied the environmental education subject in the usual way).                                                                                                                        The researcher used the experimental approach because it is suitable for the purpose and hypothesis of the research, and adopted the partial control design for two equal groups with a post-test.                   The current research was limited to the students of the first stage / Department of Educational and Psychological Sciences / College of Education and the second semester of the academic year 2022/2023, and the chapters (fourth, fifth, sixth) of environmental education.       Two divisions were chosen by a simple random drawing method, as division (a) was chosen for the experimental group that studied the environmental subject using the survey strategy, and division (b) for the control group that studied in the usual way. The number of students in the sample was (60) students, with (30) students for the experimental group and (30) ) students of the control group. The students of the two research groups were rewarded in the variables (testing the previous information in the subject of environmental education, grades of the subject of environmental education in the first semester, the chronological age calculated in months, and the tribal test for the previous information).   The research tool was applied at the end of the semester, as the researcher adopted an achievement test (Al-Qaisi, 2012) within the limits of the research, consisting of (40) items, including (30) multiple-choice items with (4) alternatives, and (10) items of pans type.             The statistical results using (SPSS) showed the following.                        :There is a statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group and the control group, in favor of the experimental group in the achievement test.                                                                                                 The researcher recommended using the survey strategy in teaching environmental education and including it in the curricula of preparing students of the College of Education for Human Sciences, especially in the subject of curricula and teaching methods.                                          .The researcher suggested conducting other researches to identify the impact of the survey strategy on other dependent variables in educational psychology, in the subject of measurement and evaluation, and for different subjects and stages.
Keywords: survey strategy , achievement , environment education